Impact of sensory processing difficulties on academic performance and occupational balance in university students (PREstEO): Protocol for a cross-sectional and longitudinal study - Daniel Prieto-Botella; Paula Peral-Gómez; Alicia Sánchez-Pérez; Berta Gándara-Gafo; Cátia Couço-Lucas; Paulo Fernandes; Sergio Serrada-Tejeda; Daniel Lloret; Paula Fernández-Pires (PLoS ONE, 2026)
Background Sensory processing difficulties (SPD) could significantly impact the daily functioning of university students, potentially affecting their academic performance and occupational balance (OB). However, this critical issue remains underexplored in the literature. The PREstEO study aims to investigate the association between SPD, OB, and academic performance among first-year university students and throughout their undergraduate studies. Additionally, the study will assess the prevalence of SPD and its associated factors in this population. Materials and methods PREstEO is a longitudinal observational cohort study conducted at the Miguel Hernández University, Spain. The study aims to recruit first-year students (from September–October 2025) and follow them over four years (2025–2029). SPD will be assessed using the Adolescent/Adult Sensory Profile (AASP), while OB and academic performance will be measured using the Occupational Balance Questionnaire (OBQ-E) and students’ grade point average (GPA), respectively. Secondary measures include psychological distress, impulsivity, sleep quality, and problematic use of videogames, the internet, and psychoactive substances. Recruitment will involve in-person invitations and institutional media campaigns. Follow-ups will be conducted annually. Statistical analyses will include robust multiple linear regressions and generalized linear mixed models, adjusting for relevant sociodemographic and behavioral factors. Discussion By adopting a longitudinal approach, PREstEO will provide novel insights into how sensory processing patterns interact with students’ daily lives over time. The findings will help to build strategies to enhance university students’ well-being and academic success.